2019
DOI: 10.1039/c9ra03537k
|View full text |Cite
|
Sign up to set email alerts
|

Colour-tunable ultralong organic phosphorescence upon temperature stimulus

Abstract: A new class of single-component molecular crystal with colour-tunable ultralong organic phosphorescence (UOP) was designed and synthesized through alkyl chain engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Supramolecular systems with dynamic noncovalent contacts provide an opportunity for the development of responsive materials as the relatively weak and reversible interactions are easy to manipulate through external agents. Single-component crystalline materials have been studied for their stimuli-responsive behaviors in good detail, and structure–property studies attribute the dynamic nature to packing changes triggered by flexible intermolecular interactions. Multicomponent crystals on the other hand provide more opportunities vis-à-vis design and fine-tuning of the property but are less explored. Yan and Li et al have reported the fluorescent cocrystals of naphthylvinylpyridine and tetra-fluoroterephthalic acid that display different mechanical responses by using light as external stimuli .…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular systems with dynamic noncovalent contacts provide an opportunity for the development of responsive materials as the relatively weak and reversible interactions are easy to manipulate through external agents. Single-component crystalline materials have been studied for their stimuli-responsive behaviors in good detail, and structure–property studies attribute the dynamic nature to packing changes triggered by flexible intermolecular interactions. Multicomponent crystals on the other hand provide more opportunities vis-à-vis design and fine-tuning of the property but are less explored. Yan and Li et al have reported the fluorescent cocrystals of naphthylvinylpyridine and tetra-fluoroterephthalic acid that display different mechanical responses by using light as external stimuli .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] However, it is still a challenge to realize high RTP performance in organic materials owing to their weak spin–orbit coupling and dominant nonradiative transition of triplet excitons. [ 3–6 ] Numerous efforts have been devoted toward the achievement of high RTP performance, including crystal engineering, [ 7–9 ] self‐assembly, [ 10–13 ] host–guest doping, [ 14–17 ] and polymerization. [ 18–25 ] In a rigid environment, the nonradiative transition of organic phosphors could be largely restricted, thus successfully realizing RTP emission in a series of organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] Consequently, many attractive metal-free RTP materials, including crystalline small molecules, [23][24][25][26] amorphous polymers, [18,[27][28][29][30][31][32] and organic/inorganic hybrid materials, [33][34][35][36][37][38] have been developed taking advantage of the weak nonradiative transition of organic phosphors in rigid microenvironments. [39][40][41][42][43][44][45] Generally, organic phosphors showed efficient phosphorescence at low temperatures because they are ossified. [46][47][48][49][50][51] However, the influence of water, oxygen, temperature, and light on metal-free RTP materials is non-negligible, significantly limiting their potential applications.…”
Section: Introductionmentioning
confidence: 99%